The requirements Of The Application Of Total Quality Management In The Conduct Of The Institute Of Sciences And Techniques Of Physical Activity And Sports At The University OfBouiraFrom The Point Of View Of Administrators - Hafsi, Salih; Lounas, Abdellah (sports creativity, 2025)
The study aimed to know The relationship between Availability of comprehensive quality management requirements ( Organizational culture , Administrative leadership, Manpower) And their application in I-STAPS at Bouira University. The researcher used the descriptive method For its convenience to the nature of the study. The sample stady included 40 employees( Administrators, Academics with administrative ranks). The sample was intentionally chosen, The researcher used the questionnaire To collect data, Where he reached the following results: - The presence of a statistically significant relationship In the answers of the sample members About the availability of comprehensive quality management requirements and its applications at I-STAPS at Bouira University . - There were no statistically significant differences in the answers of the sample members about the availability of comprehensive quality management requirements attributed to the gender variable. - There were no statistically significant differences in the answers of the sample members about the availability of comprehensive quality management re